Exposure to Leadership WalkRounds in neonatal intensive care units is associated with a better patient safety culture and less caregiver burnout. Issue 10 (13th May 2014) - Sexton, J Bryan; Sharek, Paul J; Thomas, Eric J; Gould, Jeffrey B; Nisbet, Courtney C; Amspoker, Amber B; Kowalkowski, Mark A; Schwendimann, René; Profit, Jochen
Abstract : Background: Leadership WalkRounds ( WR ) are widely used in healthcare organisations to improve patient safety. The relationship between WR and caregiver assessments of patient safety culture, and healthcare worker burnout is unknown. Methods: This cross-sectional survey study evaluated the association between receiving feedback about actions taken as a result of WR and healthcare worker assessments of patient safety culture and burnout across 44 neonatal intensive care units (NICUs) actively participating in a structured delivery room management quality improvement initiative. Results: Of 3294 administered surveys, 2073 were returned for an overall response rate of 62.9%. More WR feedback was associated with better safety culture results and lower burnout rates in the NICUs. Participation in WR and receiving feedback about WR were less common in NICUs than in a benchmarking comparison of adult clinical areas. Conclusions: WR are linked to patient safety and burnout. In NICUs, where they occurred more often, the workplace appears to be a better place to deliver and to receive care.